Help‐seeking behavior of male victims of intimate partner violence in Japan - Junko Morishita; Manabu Yasuda; Shiro Suda (PCN Reports)
Abstract Aim Intimate partner violence (IPV) is becoming a serious public health issue worldwide. This study sought to analyze factors affecting the help‐seeking behavior of male victims of IPV using a web survey. Methods Male IPV victims living in Japan were recruited to participate in a web‐based questionnaire survey conducted on February 25 and 26, 2021. A total of 1466 men were divided into two groups: Group 1 (43 men) consisted of victims who sought help and Group 2 consisted of victims (1423 men) who had not sought help. The Domestic Violence Screening Inventory, a 20‐item questionnaire regarding IPV exposure, and the Patient Health Questionnaire‐9 were used, along with the questions regarding help‐seeking behaviors for Group 1. Results Of the 43 victims, 28 victims (65.1%) used exclusively informal supports, eight victims (18.6%) used exclusively formal supports, and seven victims (16.3%) used both. Logistic regression analyses revealed that only physical violence was significantly associated with help‐seeking behaviors among types of abuse/violence (odds ratio [OR] = 4.51, confidence interval [CI] = 1.95–10.50, P < .001). Of past experiences, “foregoing divorce to avoid adverse childhood experiences in their offspring” (OR = 3.14, CI = 1.45–6.82, P = .003) was the most significantly associated with help‐seeking behaviors. Conclusion In Japan, male IPV victims tend to seek help following physical violence, but males are less are likely to seek help for nonphysical victimization, highlighting the need for targeted support for victims of nonphysical abuse. To provide comprehensive aid to male IPV victims, consultation centers designed for men will be needed.